Choose a school based on your child. (Journal of Parents and Teachers, 2025)
The article argues that the educational process is an experience of communication and personal connection among all members of the educational community. Additionally, it emphasizes the importance of the attitude and action of listening, as listening is an art that everyone should feel and practice through the development of technique.
Keywords: educational process; listening; attitude